Analysis Effectiveness of Ecotourism-Based Mangrove Management in the Pangkal Babu Area, West Tanjung Jabung, Jambi - Winarni, Etik; Sari, Yolanda; Putra, Iwan Eka; Mustika, Mustika; Andrila, Novia (FKIP Universitas Jambi, 2026)
The mangrove ecosystem is one of the natural resources that has significant potential to be developed as a tourism attraction. The management of mangrove areas can be enhanced through ecotourism-based activities. Ecotourism is a form of educational tourism that emphasizes human behavior in preserving the environment sustainably, while also providing economic benefits and environmental services without excessive exploitation of mangroves. The use of environmental services based on ecotourism supports the sustainability of mangrove ecosystems as buffer zones for conservation areas. In addition, ecotourism-based environmental services encourage the long-term sustainability of mangrove ecosystems as protective zones for conservation areas. The management of mangroves for ecotourism is also in line with the shifting preferences of tourists from conventional tourism. This study aims to evaluate the effectiveness of ecotourism-based mangrove management, which can later serve as a reference for government policy decision-makers. Data collection in this study was conducted through field surveys by distributing questionnaires, using an effectiveness approach based on five indicators proposed by Siagian: input, output, outcome, benefit, and impact. The research involved field observations and questionnaire distribution using a Likert scale. The analysis method employed is the measurement of effectiveness by applying the effectiveness formula. The findings of this study reveal that: (1) The input indicator is, on average, categorized as moderately effective. (2) The output indicator is, on average, categorized as moderately effective. (3) The outcome indicator is, on average, categorized as moderately effective. (4) The benefit indicator is, on average, categorized as moderately effective. (5) The impact indicator is, on average, categorized as ineffective.